2020
DOI: 10.1103/physrevlett.125.131601
|View full text |Cite
|
Sign up to set email alerts
|

Unreasonable Effectiveness of Higher Derivative Supergravity in AdS4 Holography

Abstract: We study four-derivative corrections to four-dimensional N ¼ 2 minimal gauged supergravity controlled by two real constants. The solutions of the equations of motion in the two-derivative theory are not modified by the higher-derivative corrections. We use this to derive a general formula for the regularized on-shell action for any asymptotically locally AdS 4 solution of the theory and show how the higher-derivative corrections affect black hole thermodynamic quantities in a universal way. We employ our resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 50 publications
(103 reference statements)
9
87
0
Order By: Relevance
“…This relation implies infinite relations between derivatives of F (b; m I ) evaluated at m = 0, b = 1, such as the fact that all four derivatives can be written in terms of the six quantities listed in (1.2). For the N = 8 ABJ(M) theories, these relations allowed us to compute ∂ 4 b F (b; m I ) and ∂ 5 b F (b; m I ) to all orders in 1/N , which at sub-leading order match the prediction given in (1.3) from M-theory compactified on AdS 4 × S 7 /Z k and expanded to leading order beyond the supergravity limit [21]. Our results provide constraints at further orders in 1/N that will allow more higher derivative corrections to supergravity to be derived following the program outlined in [21].…”
Section: Jhep04(2021)244 5 Conclusionmentioning
confidence: 74%
See 3 more Smart Citations
“…This relation implies infinite relations between derivatives of F (b; m I ) evaluated at m = 0, b = 1, such as the fact that all four derivatives can be written in terms of the six quantities listed in (1.2). For the N = 8 ABJ(M) theories, these relations allowed us to compute ∂ 4 b F (b; m I ) and ∂ 5 b F (b; m I ) to all orders in 1/N , which at sub-leading order match the prediction given in (1.3) from M-theory compactified on AdS 4 × S 7 /Z k and expanded to leading order beyond the supergravity limit [21]. Our results provide constraints at further orders in 1/N that will allow more higher derivative corrections to supergravity to be derived following the program outlined in [21].…”
Section: Jhep04(2021)244 5 Conclusionmentioning
confidence: 74%
“…The first higher derivative corrections, i.e. the four derivative terms, were recently derived in [21] for any minimal N = 2 gauged supergravity on AdS 4 in terms of two theory dependent coefficients. These coefficients were then fixed for the ABJ(M) M-theory dual at finite k using the large N results for F (1, 0) and the coefficient c T of the stress tensor two-point function, which was computed using ∂ 2 m ± F in [22].…”
Section: Jhep04(2021)244mentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown in [60] that the central charge of the near-horizon asymptotic Virasoro symmetry also gets modified in the gravity with higher-derivative terms, while the Frolov-Thorne temperature and the Cardy formula still hold. Other higher-derivative aspects of AdS 4 black holes were recently considered [61,62]. A tantalizing property of higher-derivative corrections in AdS 5 black holes was recently reported in [63], which showed that the leading α -correction is absent in the BPS limit.…”
Section: Discussionmentioning
confidence: 99%